Resistir obedeciendo. Para una etnografía de la resistencia civil no armada en Medellín (2010)
ABSTRACT: This article intends to show that a civilian population dominated by armed actors does not always become the passive victim of violence and armed aggression, nor is its attitude inevitably that of submissive loyalty in the face of domination by armed actors. The objective is to illustrate how in urban contexts like the city of Medellin, marked by the control, domination and violence of armed actors in conflict, poor neighborhood communities have tried many and varied unarmed civil resistance actions in the face of that domination by armed actors over their territories and community. In other words, it aims to show that in the scenario and the social, political, economic and cultural dynamics of urban territories, the protagonists are not only armed actors, but also neighborhood communities that oppose resistance to this domination using their leadership and collective actions, which are often illegal, secret or simulated. The core of this article is the summary of two narratives by neighborhood leaders in “Commune 9,” which claim to relate some of these community experiences of unarmed civil resistance.